2023
DOI: 10.1097/gox.0000000000004790
|View full text |Cite
|
Sign up to set email alerts
|

Parents of Children with Cleft Lip Exhibit Heightened Visual Attention to the Perioral Area

Abstract: Background: Following high-quality surgical repair, children born with a cleft lip anomaly may still display lasting visual differences. We exposed control adults and parents of affected children to images of children with cleft deformity and compared their visual tracking patterns. The protocol investigated whether parental exposure to secondary cleft deformity heightens or diminishes visual attraction to this type of structural facial variation. Method: Twenty participants (10 control adults, 10 parents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous reports have demonstrated that cleft-repaired faces were rated as less attractive than non-cleft controls, with greater visual attention to the cleft-affected look-zones 13 . In addition, parents of children with clefts demonstrate heightened attention to these facial differences compared with the naïve observer 14 . Patient-reported outcome metrics have not previously been linked to specific orthognathic surgical movements.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports have demonstrated that cleft-repaired faces were rated as less attractive than non-cleft controls, with greater visual attention to the cleft-affected look-zones 13 . In addition, parents of children with clefts demonstrate heightened attention to these facial differences compared with the naïve observer 14 . Patient-reported outcome metrics have not previously been linked to specific orthognathic surgical movements.…”
Section: Discussionmentioning
confidence: 98%
“…13 In addition, parents of children with clefts demonstrate heightened attention to these facial differences compared with the naïve observer. 14 Patientreported outcome metrics have not previously been linked to specific orthognathic surgical movements. Here, we demonstrate correlations between skeletal orthognathic movements and both observer perceptions, as well as PROs in patients with CLP.…”
Section: Discussionmentioning
confidence: 99%